Pengaruh Ekstrak Buah Delima Terstandar 40% Ellagic Acid terhadap Profil Darah Tikus Putih Yang Mengalami Nefrotoksisitas akibat Induksi Gentamisin - Bambang Sektiari Lukiswanto; Wiwik Misaco Yuniarti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
The purpose of this study was to determine the effect of pomegranate extract of 40% ellagic acid on blood profile of albino rats that had nephrotoxicity after included with Gentamicin. a total of 32 white rats were divided into four treatment groups, each consisting of eight rats. the four treatment groups were healthy rats (P0), Gentamicin induced rats (P1), Gentamicin induced rats and ellagic acid treatment (P2) and Gentamicin induced rats and standardized Pomegranate extract therapy 40% ellagic acid treatment (P3). After seven days of treatment, blood was taken for blood profile tests. The results showed that in the Gentamicin-induced group (P0), a decrease in blood profile allegedly caused by Gentamicin that could cause damage and impaired renal tubular function. Givibg ellagic acid and pomegranate extracts of 40% ellagic acid proved to improve the blood profile of Gentamicin induced rats. This is due to inhibition of renal damage and improved renal function due to antioxidant activity possessed by ellagic acid and pomegranate extract of standardized 40% ellagic acid.